EFFECT OF COAL RATIO ON THE HIGH-LEAD SLAG REDUCTION PROCESS - Zhang, Zhongtang; Li, Weifeng; Zhan, Jing (Journal of Mining and Metallurgy, Section B: Metallurgy, 2018)
The effect of coal ratio on the high-lead slag reduction process was reported in this article. The density, melting temperature, viscosity, chemical composition and phase transformation of the reducing slag at different coal ratios were investigated. The results indicated that the density and viscosity of the reducing slag and the content of lead and copper in reducing slag decreased while the content of iron, silicon, calcium and zinc in reducing slag increased as the coal ratio increased. The melting temperature of the reducing slag increased sharply when the coal ratio varied in the range of 1.5% to 3%. The technological mineralogy of the reducing slag at different coal ratios indicated that lead mainly exists in reducing slag in the form of metallic lead. The industrial verification test results showed that the average recovery rate of the lead was above 96.0%, the average lead content in the reducing slag was less than 2.0% and the average fume rate was about 12.0%.